Effect of Immersion Concentration in Salt Solution, Drying Time and Air Velocity on Drying Wet Noodles Using a Tray Dryer and Solar Assistance - Maktum Muharja; Siska Nuri Fadilah; Achri Isnan Khamil; Rizki Fitria Darmayanti; Ditta Kharisma Yolanda Putri; Meta Fitri Rizkiana; Viqhi Aswie; Badril Azhar (Politeknik Negeri Malang, 2023)
The noodles in the market are dry noodles with 8-10% water content. Dried noodles have a longer shelf life because they are less prone to mold growth. Drying noodles with the help of the sun and tray dryers are currently an option because they are efficient and do not require a lot of energy. Reduction of water content is also optimized by soaking wet noodles in salt water. This study aims to determine the effect of soaking noodles in salt water and the flow rate to decrease the water content of noodles. The study began with soaking wet noodles in a salt solution with a variation of 50-150 g/L, then dried for 1 hour using a hybrid method and tray dryer with a flow rate variation of 1.2-3.3 m/s. Observations were made at intervals of 0-1 hour. The results showed that the time and speed of the flow rate can reduce the humidity in the drying chamber of the tray dryer. The lowest water content reduction of up to 11% was obtained when soaking wet noodles in 150 g/L salt solution and at the highest flow rate of 3.3 m/s. The ANOVA results show that the drying method with tray dryer is more optimal than hybrid drying. Thus, this method can be a solution to optimize the noodle drying process quickly and efficiently.